1999
DOI: 10.1023/a:1022214710054
|View full text |Cite
|
Sign up to set email alerts
|

Giving and Receiving Help: Interpersonal Transactions in Mutual‐Help Meetings and Psychosocial Adjustment of Members

Abstract: The helping transactions that occur in group meetings have been theorized to be important therapeutic mechanisms within mutual-help (or self-help) groups. Hypothesized links between giving and receiving help and psychosocial adjustment were examined in a mutual-help group for individuals with serious mental illness (GROW). Participants' adjustment was assessed at two time points and helping behaviors were measured with observational coding of weekly group interactions during the period between assessments. Fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(97 citation statements)
references
References 48 publications
5
90
0
2
Order By: Relevance
“…These characteristics were corroborated in a qualitative longitudinal study in which Ochocka and colleagues described COSPs as safe and welcoming environments and social arenas that offer opportunities to interact with peers and connect with the community at large [9]. At least one sociologist further posited the "helper-therapy" principle, i.e., the opportunity to help others and receive benefits in the process [10], which has been demonstrated empirically within the peer support field and the general population [11][12]. Weaver Randall and Salem described the "active ingredients" of self-and mutual-help programs [13].…”
Section: Introductionmentioning
confidence: 89%
“…These characteristics were corroborated in a qualitative longitudinal study in which Ochocka and colleagues described COSPs as safe and welcoming environments and social arenas that offer opportunities to interact with peers and connect with the community at large [9]. At least one sociologist further posited the "helper-therapy" principle, i.e., the opportunity to help others and receive benefits in the process [10], which has been demonstrated empirically within the peer support field and the general population [11][12]. Weaver Randall and Salem described the "active ingredients" of self-and mutual-help programs [13].…”
Section: Introductionmentioning
confidence: 89%
“…In a well-designed longitudinal study of groups for people with serious mental illness, Roberts et al (1999) found improvement over a one-year period on measures of psychological Mutual help groups, p.12 symptoms and social adjustment. A particular strength of the study was that it examined associations between interpersonal transactions during meetings (using observer ratings) and the outcome variables.…”
Section: Groups For Chronic Mental Illnessmentioning
confidence: 99%
“…Another promising direction is the examination of how group process variables, such as levels of self-disclosure and of giving and receiving help, relate to outcomes (Roberts et al, 1999). Research focusing on such process variables might take several forms including behavioral observations of the type conducted by Roberts et al as well as in-depth qualitative studies investigating members' experiences of participation and change.…”
Section: Recommendations For Future Researchmentioning
confidence: 99%
“…Cognitive remediation studies indicate that self-esteem, among other variables, increases when paper-and-pencil learning is used to help individuals diagnosed with schizophrenia take an organized, conscious approach to information processing [66]. Cognitive reframing has been used in psychotherapy with individuals in an SE program to shift perspectives about negative work experiences that might affect tenure in employment [67][68], as well as in peer-support programs such as GROW, in which reframing was found to be associated with better social adjustment [69]. Cognitive enhancement therapies use "mentalizing" to help individuals understand mental states not only in themselves but also in others [70], which has been found to be exceptionally important for those recovering from a first episode of a serious mental illness [71].…”
Section: What Does Research Evidence Indicate?mentioning
confidence: 99%